English Teachers’ Perspectives towards the Implementation of Differentiated Instruction in the Classroom - Rahmani, Eka Fajar (English Education Department at FKIP Nommensen University, 2024)
This study aims to explore the perspectives of junior high school English teachers in Kalimantan Barat on the implementation of differentiated instruction (DI) in culturally and linguistically diverse classrooms. Using a descriptive survey method, data were gathered from 108 teachers through a validated closed-ended questionnaire. The findings reveal that while teachers generally possess a strong understanding of DI and hold positive beliefs about its effectiveness, its application varies, particularly in addressing students' readiness, interests, and learning profiles. Key barriers include limited resources, large class sizes, and insufficient administrative support. The study highlights the need for targeted professional development and resource allocation to support DI implementation. Recommendations include improving training programs and increasing support from school administrations. Limitations of the study include a focus on one geographic region, which may limit the generalizability of the findings. These insights are relevant for enhancing DI practices in similarly diverse educational settings.